2013
DOI: 10.2147/tcrm.s41131
|View full text |Cite
|
Sign up to set email alerts
|

Cefditoren versus levofloxacin in patients with exacerbations of chronic bronchitis: serum inflammatory biomarkers, clinical efficacy, and microbiological eradication

Abstract: BackgroundThe aim of this open-label, randomized, parallel-group pilot study was to evaluate the efficacy of cefditoren pivoxil and levofloxacin in terms of speed of reduction in inflammatory parameters, clinical recovery, and microbiological eradication.MethodsForty eligible patients with acute exacerbation of chronic bronchitis (AECB) were randomized to receive cefditoren 200 mg twice a day for 5 days (n = 20) or levofloxacin 500 mg once daily for 7 days (n = 20).ResultsThe inflammatory parameters which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
0
11
0
1
Order By: Relevance
“…Finally, only 48 of the 86 articles, with a total of 14,448 participants were retrieved. 2 , 4 , 12 21 , 34 69 Among the 48 studies, 29 of the randomized trials were double blind, 5 were single blind, and the others were open-label or unspecified. The most popular treatments assessed were quinolones and macrolides.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, only 48 of the 86 articles, with a total of 14,448 participants were retrieved. 2 , 4 , 12 21 , 34 69 Among the 48 studies, 29 of the randomized trials were double blind, 5 were single blind, and the others were open-label or unspecified. The most popular treatments assessed were quinolones and macrolides.…”
Section: Resultsmentioning
confidence: 99%
“…A probability model of therapeutic outcomes predicted that cefditoren pivoxil was almost equally effective to levofloxacin for the treatment of acute exacerbations of COPD in patients with mildmoderate disease, but that it was less effective in patients with severe disease [27]. Recently, a direct comparative study also reported comparable efficacy between cefditoren pivoxil (200 mg twice daily for 5 days; 80% cure rate) and levofloxacin (500 mg once daily for 7 days; 75% cure rate) for the treatment of exacerbations in patients with chronic bronchitis [22]. The higher severity of COPD in the present study, with the patients typically having a causative factor for refractory severe infection, likely accounts for our lower cure rate of 65.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical antibiotic treatment is usually initiated with a penicillinebeta-lactamase inhibitor combination, a macrolide, or a quinolone [1,20]. Several studies have also reported the potential efficacy of cefditoren pivoxil, a cephalosporin [21,22]. However, no studies have evaluated its clinical efficacy for the treatment of acute exacerbations in Japanese patients, who are mostly older and have lower body mass indexes compared with their non-Asian peers.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics active against planktonic cells and able to interfere or decrease biofilm development may offer clinical advantages [ 125 ]. Additionally, the use of antibiotics may also reduce inflammatory parameters [ 107 ]. Cefditoren showed to interfere biofilm formation in a study comparing cefditoren (0.03 mg/l) with amoxicillin/clavulanic acid (1/0.5 mg/l) that concluded that both compounds were able to reduce biofilm formation by the 10 pneumococcal isolates tested, with significant higher reductions in the case of cefditoren [ 126 ].…”
Section: From Pk/pd Interpretation To Clinical Data In Adultsmentioning
confidence: 99%
“…Cefditoren showed to interfere biofilm formation in a study comparing cefditoren (0.03 mg/l) with amoxicillin/clavulanic acid (1/0.5 mg/l) that concluded that both compounds were able to reduce biofilm formation by the 10 pneumococcal isolates tested, with significant higher reductions in the case of cefditoren [ 126 ]. With respect to inflammation, one study comparing cefditoren and levofloxacin found that the use of both antimicrobials was associated with significant reductions of IL-6 and KL-6, two mediators of lung inflammation and epithelial damage [ 107 , 127 ].…”
Section: From Pk/pd Interpretation To Clinical Data In Adultsmentioning
confidence: 99%